Inequality confirmed: institutional exclusion in the interaction between job-centre advisors and unemployed young people - Ulla Rantakeisu; Kirsti Kuusela; Lis-Bodil Karlsson (Nordic Journal of Social Research)
Since the 1990s, the pressures on the unemployed have intensified in Sweden owing to increasing demands on individuals to be employable. This article centres on unemployed youths’ experiences of their visits to the public employment services in four Swedish municipalities and how these experiences can be understood against the background of the intersection of social class and gender. A total of 18 unemployed youths were interviewed and their reasoning was compared with their respective employment-agency officers. The analysis shows that the employment agency gives priority to young working-class men over young working-class women and to middle-class youths over working-class youths, respectively. Young working-class women’s wish to combine employment with caregiving is seen as an encumbrance by the employment agency and these women expressed the harshest criticism against the employment agency. When the advisors meet youths who do not correspond with the current expectations and ideals of the labour market, they risk taking part in an institutional process of exclusion of these youngsters.